The design issue of local SME food and beverage product labelling and packaging: designers versus audience perspectives / Wan Alia Najiha Wan Mahmud - Wan Mahmud, Wan Alia Najiha (2022)
The purpose of this study is to study the current design issue of SME food and beverage product labelling and packaging in Malaysia. Packaging has become a vital means for a differentiating item, and it also can attract consumer attention. Packaging is now an important aspect in marketing and is treated as one of the most influential factors concerning consumer purchase decision at the point of purchase. Qualitative approaches through semi-structured interview were used as data collection. The results of the analysis show that among all the packaging attributes, information concerning the packaging and the shape of the packaging has a significant impact on the purchase decision of processed foods. Interestingly, attributes, such as graphics, size, colour, and material, were not significant in influencing the purchase decision of processed packaged foods.